2017
DOI: 10.1016/j.cardfail.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Truncating Titin ( TTN) Variants in Chemotherapy-Induced Cardiomyopathy

Abstract: Chemotherapy-induced cardiomyopathy (CCMP) is a complication of chemotherapy treatment occurring in 9% of patients treated with the use of anthracyclines. Currently, risk stratification is based on clinical risk factors that do not adequately account for variable individual susceptibility. This suggests the presence of other determinants. In this case series, we describe 2 women with breast cancer who developed severe heart failure within months after chemotherapy. Genetic screening revealed truncating framesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 13 publications
0
45
1
2
Order By: Relevance
“…It should be noted that the case of dilated cardiomyopathy which develops after a myocardial infarction or ischemia is often classified as a separate disease entity: ischemic cardiomyopathy (ICM) [25,28,29,30,31]. The environmental cases can also have genetic predisposition [32,33]. If known cause is not identified, DCM is called idiopathic DCM.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the case of dilated cardiomyopathy which develops after a myocardial infarction or ischemia is often classified as a separate disease entity: ischemic cardiomyopathy (ICM) [25,28,29,30,31]. The environmental cases can also have genetic predisposition [32,33]. If known cause is not identified, DCM is called idiopathic DCM.…”
Section: Introductionmentioning
confidence: 99%
“…However, patient data from breast cancer patients shows that cancer drugs can cause frameshift mutation in titin, reducing cardiac compliance and ultimately leading to cardiomyopathy. [ 186 ] More studies are needed to understand the cardiotoxic effects of chemotherapeutic and other cardiotoxic agents on CM stiffness to understand the mechanisms by which these compounds induce these changes.…”
Section: Measuring Changes To CM Stiffness In Response To Cardiotoxicmentioning
confidence: 99%
“…However, reports from studies in rabbits and humans have demonstrated altered expression of integrins and titin genes, respectively, in response to cancer drug treatment. [ 186,192 ] In both cases, rabbits and humans developed heart failure. While it is unclear if the changes in the gene expression of integrins and titin resulted in altered protein function leading to any causal effects, it is widely known that changes in the function of integrins and/or titin can impact contractility and the transmission of mechanical signals.…”
Section: Mechanotransduction and Cardiotoxicitymentioning
confidence: 99%
“…Late cardiotoxicity was mainly related to high cumulative dosage, however, genetic factors play an important role in the occurrence of cardiotoxicity in patients with low-to moderate-dose of chemotherapy drugs, especially in patients with relatively low cumulative dose of adjuvant therapy [3][4][5][6]. Single nucleotide polymorphisms (SNPs) are the research focus for the genetic susceptibility to cardiotoxicity [7].…”
Section: Introductionmentioning
confidence: 99%